2020
DOI: 10.1177/0030222820919253
|View full text |Cite
|
Sign up to set email alerts
|

Cremation and Grief: Are Ways of Commemorating the Dead Related to Adjustment Over Time?

Abstract: Funeral services are known to serve multiple functions for bereaved persons. There is also a common, intuitively reasonable assumption of positive associations between engaging in funeral activities and adjustment to bereavement. We examined whether restricting ceremonial cremation arrangements to a minimum has a negative association with grief over time. Bereaved persons in the United Kingdom completed questionnaires 2 to 5 months postloss and again a year later ( N = 233 with complete data; dropout = 11.4%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…12 Most recently, a study in the United Kingdom found satisfaction with funeral arrangements to be typically high, recognising that funeral services fulfil multiple functions for bereaved persons. 30 There is evidence to suggest that not attending a funeral or a lack of participation in memorialisation practices may lead to poorer grief adjustment and bereavement outcomes, seen in children 31 not allowed to attend funerals and adults prohibited due to incarceration. 32 More research is needed to understand the impact of altered funeral practices during COVID-19 on the mental health and grief experience of those bereaved.…”
Section: Memorialisation Practices Pre-covid-19mentioning
confidence: 99%
“…12 Most recently, a study in the United Kingdom found satisfaction with funeral arrangements to be typically high, recognising that funeral services fulfil multiple functions for bereaved persons. 30 There is evidence to suggest that not attending a funeral or a lack of participation in memorialisation practices may lead to poorer grief adjustment and bereavement outcomes, seen in children 31 not allowed to attend funerals and adults prohibited due to incarceration. 32 More research is needed to understand the impact of altered funeral practices during COVID-19 on the mental health and grief experience of those bereaved.…”
Section: Memorialisation Practices Pre-covid-19mentioning
confidence: 99%
“…Evidence from recent studies -in non COVID-29 circumstances -suggests that the type of ceremony may not be so critical to bereavement outcome. Studies have not shown significant relationships between elaborateness of funerals with grief and grieving over time (Birrell et al, 2020;Burrell & Selman, 2020;Mitima-Verloop et al, 2019). Whether or not such findings are replicated in the case of pandemic restrictions -with the notable difference that the regulations are enforced, not chosen -is again an empirical question for further investigation.…”
Section: Limitations: Dpm Application and Further Research Directionsmentioning
confidence: 97%
“…Previous research introduced above suggests that satisfying funerals can buffer bereavement grief, through religious rituals, faith, and social support, while and Birrell (2020) found no such correlations. We were unable to show that positive appraisals of funerals result in positive health and productivity, but we did find that negative appraisals and abbreviated funerals correlated with lower productivity and higher medical/social service costs thereafter.…”
Section: Hypothesis 2: Effects Of Funeral Dissatisfaction On Productimentioning
confidence: 80%